Zinc Maintains Embryonic Stem Cell Pluripotency and Multilineage Differentiation Potential via AKT Activation - Mnatsakanyan, Hayk; Sabater i Serra, Roser; Salmeron-Sanchez, Manuel; Rico, Patricia (Frontiers in Cell and Developmental Biology, 2019)
Embryonic stem cells (ESCs) possess remarkable abilities, as they can differentiate into all cell types (pluripotency) and be self-renewing, giving rise to two identical cells. These characteristics make ESCs a powerful research tool in fundamental embryogenesis as well as candidates for use in regenerative medicine. Significant efforts have been devoted to developing protocols to control ESC fate, including soluble and complex cocktails of growth factors and small molecules seeking to activate/inhibit key signaling pathways for the maintenance of pluripotency states or activate differentiation. Here we describe a novel method for the effective maintenance of mouse ESCs, avoiding the supplementation of complex inhibitory cocktails or cytokines, e.g., LIF. We show that the addition of zinc to ESC cultures leads to a stable pluripotent state that shares biochemical, transcriptional and karyotypic features with the classical LIF treatment. We demonstrate for the first time that ESCs maintained in long-term cultures with added zinc, are capable of sustaining a stable ESCs pluripotent phenotype, as well as differentiating efficiently upon external stimulation. We show that zinc promotes long-term ESC self-renewal (>30 days) via activation of ZIP7 and AKT signaling pathways. Furthermore, the combination of zinc with LIF results in a synergistic effect that enhances LIF effects, increases AKT and STAT3 activity, promotes the expression of pluripotency regulators and avoids the expression of differentiation markers.